DESIGNING NORTH SUMATRA PROVINCIAL LIBRARY WITH GREEN ARCHITECTURE APPROACH IN MEDAN CITY - Tampubolon, Ihsnaul Majid; Siahaan , Nelson Manumpak (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
Indonesia is one of the countries that has a low interest in reading. This is concluded from the results of the “Most Littered Nation In the World” research conducted by Central Connecticut State University in March 2016, which states that Indonesia is ranked 60th out of 61 countries regarding reading interest (Devega, 2017).In addition, according to data from Siswati (2010:124), the IAEEA publication dated November 28, 2007 on reading interest from 41 countries shows that the reading ability of Indonesians is comparable to the southern hemisphere countries of New Zealand and South Africa. According to BPS in 2006, Indonesians still do not use reading as a way to get information. They found that 85.9 percent of Indonesians would rather watch television and listen to the radio than read (23.5 percent). This means that 23.5 percent of Indonesians read to get new information. This data shows that people do not need to read.To address the existing problems, the North Sumatra Provincial Library will be designed with a green architecture approach based on information and communication technology, in order to support the library’s function as an information center with recreational nuances that are expected to be enjoyed by the entire community so as to realize a modern library that can keep up with the times